Age is an independent predictor of outcome in endometrial cancer patients: An Israeli Gynecology Oncology Group cohort study. (30th October 2020) - Hag‐Yahia, Nasreen; Gemer, Ofer; Eitan, Ram; Raban, Oded; Vaknin, Zvi; Levy, Tally; Leytes, Sofia; Lavie, Ofer; Ben‐Arie, Alon; Amit, Amnon; Namazov, Ahmed; Volodarsky, Michael; et al.
Abstract: Introduction: Advanced age is considered an adverse factor in endometrial cancers but may be a surrogate for other conditions that impact outcomes. The study objective was to assess the association of age with endometrial cancer features, treatment and prognosis. Material and methods: In this multicenter cohort study, consecutive women with endometrial cancer treated at 10 Israeli institutions between 2000 and 2014 were accrued in an assimilated database. Postmenopausal women were stratified into age groups with a cut‐off of 80. Clinical, pathological and treatment data were compared using t test or Mann‐Whitney test for continuous variables, and Chi‐square Test or Fisher's Exact test for categorical variables. Main outcome measures included disease recurrence and disease‐specific and overall survival; these were plotted using the Kaplan‐Meier method and compared using the log‐rank test. The association between age and recurrence and survival, adjusted for other clinical and pathological factors, was assessed using multivariable Cox regression modeling. Results: A total of 1764 postmenopausal women with endometrial cancer were identified. Adverse pathological features were more prevalent in older women, including high‐risk histologies (35% vs 27%, P = .025), deep myoinvasion (44% vs 29%, P = .001) and lymphovascular involvement (22% vs 15%, P = .024). Surgical staging was performed less frequently among older women (33% vs 56%; P < .001). Chemotherapy was less often prescribed, even for non‐endometrioid histologies (72% vs 45%; P < .001). On multivariable analysis, age remained a significant predictor for recurrence (HR = 1.75, P = .007), death of disease (HR = 1.89, P = .003) and death (HR = 2.4, P < .001). Conclusions: Older age in women with endometrial cancer is associated with more adverse disease features, limited surgery and adjuvant treatment, and worse outcomes. On multivariable analysis, age remains an independent prognosticator in this population.